Picatrix: a medieval treatise on astral magic - Maslama Ibn al-Qāsim Ibn Ibrāhīm Ibn ʿAbd Allāh Ibn Ḥātim al-Qurṭubī al-Zayyāt 905-964 (Magic in history, 2019)
An English translation, with accompanying introduction, commentary, and notes, of the medieval treatise on astrological magic known as Picatrix, a guide for constructing magical talismans, mixing magical compounds, summoning planetary spirits, and determining astrological conditions